A challenge for mutation specific risk stratification in long QT syndrome type 1. Issue 1 (July 2018) - Yagi, Noriaki; Itoh, Hideki; Hisamatsu, Takashi; Tomita, Yukinori; Kimura, Hiromi; Fujii, Yusuke; Makiyama, Takeru; Horie, Minoru; Ohno, Seiko
Highlights: Correlations between mutation location and phenotype in long QT syndrome type 1 have been well reported. Patients with V254M or S277L suffered severe cardiac symptoms. Phenotypes of long QT syndrome patients were predicted by the mutation themselves. Patients with KCNQ1 should be evaluated by their own mutations. Abstract: Background: The relationship between mutation locations in KCNQ1 which is a major gene in long QT syndrome (LQTS) and phenotype has been analyzed and used for risk stratification. Mutations in the transmembrane region (TM) or cytoplasmic-loop (C-loop) are associated with more frequent cardiac events than those in other regions. However, accumulation of LQTS type 1 (LQT1) patients poses the question of whether the location specific risk stratification is really effective. Methods: The study cohort consisted of 67 KCNQ1 mutation carriers and 13 family members who were suspected as having LQTS due to sudden cardiac death or syncope from 36 unrelated families. The KCNQ1 mutations were L250H, V254M, H258P, and R259C located in segment 4–5 linker (C-loop), G269S, and S277L in segment 5 (TM). Results: More than half of the patients with V254M or S277L suffered sudden cardiac death or syncope. In contrast, those with other mutations showed mild phenotype. In these two mutations related to severe phenotype, gender frequency and the age of onset were contrasting, 14 out of 23 patients with V254M were male, 19 out of 22 patients with S277L were female. In the patients we could confirm the age of onset, all of the patients with V254M showed symptoms at less than 15 years old, while 5 out of 12 patients with S277L suffered symptoms after 16 years old. Conclusion: Clinical characteristics were not specific for mutation locations but specific for respective mutations in our LQT1 patients. Patients should be evaluated by their own mutations to prevent severe cardiac events.